STANDARDIZATION OF COMPETITIVE ELISA FOR MEASUREMENT OF ANTIBODIES PRODUCED AGAINST STAPHYLOCOCCUS AUREUS - Khalil-ur-Rehman; Zia, M. Anjum; Parveen, Bushra; Kamal, Shagufta; Arshad, M. (Journal of Research (Science), 2004)
Formalin, heat killed Staphylococcus aureus was prepared by growing on staph-110 agar medium. Different doses of antigen were injected in rabbits and after 14 days collected the serum. Antibodies isolated by ammonium sulfate precipitation, protein contents were estimated through Biuret as well as UV methods. The antibodies were conjugated with 10 mg soybean peroxidase having activity 83.02 U mL-1 using two-step glutaraldehyde method. Conjugation was detected by competitive ELISA and best results were recorded at 1:200 dilution of the conjugates.